Antimalarial usage in pregnancy: a cross-sectional study in selected health facilities in the Brong Ahafo Region of Ghana - Fordjour, Francis (2015)
A thesis submitted to the Department of Clinical and Social Pharmacy, Kwame Nkrumah University of Science and Technology Kumasi, in partial fulfillment of the requirements for the degree of MASTER OF SCIENCE IN CLINICAL PHARMACY